Examining the Prevalence of Adverse Childhood Experiences and Associated Cardiovascular Disease Risk Factors Among Low-Income Uninsured Adults. Issue 9 (September 2019) - Allen, Heidi; Wright, Bill J.; Vartanian, Keri; Dulacki, Kristen; Li, Hsin-Fang
Abstract : Background: Adverse childhood experiences (ACEs) are linked to poor adult health outcomes, including cardiovascular disease. However, little is known about its prevalence, specifically in low-income populations. The objective of this study was to estimate the extent of ACEs in a low-income, nonclinical, uninsured adult population and assess the relationship between ACEs and cardiovascular disease risk factors. Methods and Results: This study leverages the OHIE's (Oregon Health Insurance Experiment) study population, uninsured adults who were randomly selected to apply for Medicaid, and data collected through in-person health screenings. We objectively measured obesity, cholesterol, blood pressure, and blood sugar. Smoking, physical activity, and history of chronic disease were self-reported. Independent variables were the 10-item ACEs questions covering neglect, abuse, and household dysfunction. The sample consisted of 12 229 low-income, nonelderly uninsured adults who participated in the OHIE health screenings from 2009 to 2010. A total of 5929 (48%) returned a follow-up survey reporting ACEs in 2012. ACEs were more prevalent in low-income adults compared with previous estimates in a general clinical population, with notably high rates of emotional abuse, emotional neglect, and household dysfunction. ACEs were statistically associated with higher rates of obesity, smoking, and physical inactivity, but not high cholesterol or diabetes mellitus. We detected a strong relationship between ACEs and a self-reported history of a hypertension diagnosis but no statistically significant differences in being hypertensive. Conclusions: This study design allowed us to assess the prevalence of ACEs among uninsured low-income adults and the association between ACEs and clinical indicators of cardiovascular disease risk that are difficult to ordinarily observe. Low-income adults have high rates of ACEs than previous prevalence estimates and ACEs were associated with higher rates of multiple cardiovascular disease risk factors. As states continue to expand Medicaid to the previously uninsured, providers may want to consider incorporating trauma-based approaches to care delivery. Abstract : Supplemental Digital Content is available in the text.